Modelling and characterization of cell collapse in aluminium foams during dynamic loading - Kader, Md Abdul; Islam, Md A.; Hazell, Paul J.; Escobedo, Juan P.; Saadatfar, Md; Brown, Andrew David; Appleby-Thomas, Gareth J. (Elsevier, 2016)
Plate-impact experiments have been conducted to investigate the elastic–plastic behaviour of shock wave propagation and pore collapse mechanisms of closed-cell aluminium foams. FE modelling using a meso-scale approach has been carried out with the FE software ABAQUS/Explicit. A micro-computed tomography-based foam geometry has been developed and microstructural changes with time have been investigated to explore the effects of wave propagation. Special attention has been given to the pore collapse mechanism. The effect of velocity variations on deformation has been elucidated with three different impact conditions using the plate-impact method. Free surface velocity (ufs) was measured on the rear of the sample to understand the evolution of the compaction. At low impact velocities, the free-surface velocity increased gradually, whereas an abrupt rise of free-surface velocity was found at an impact velocity of 845 m/s with a copper flyer-plate which correlates with the appearance of shock. A good correlation was found between experimental results and FE predictions.